PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK DENGAN MODEL KOOPERATIF TIPE TWO STAY TWO STRAY BERBANTUAN GEOGEBRA - Siti Khoerunnisa; Rianti Cahyani (UJMES (Uninus Journal of Mathematics Education and Science), 2021)
This study aims to determine the increase in mathematical communication skills of students who get Two Stay Two Stray (TS-TS) cooperative learning model assisted by Geogebra and students who get Teams Games Tournament (TGT) cooperative learning type. The methodology used in this research is the quasi-experimental method with the Nonequivalent Pretest-posttest Control Group Design design. The research is conducted in one of the public high schools in Bandung. The population of this research are all students of X IPA, while the sample of this research are X IPA-4 as a class TS-TS and X IPA-5 as a TGT class. The instrument used in this research is amathematical communication skills test. Based on the results of the Mann Whitney test analysis, it can be concluded that the increase in mathematical communication skills of students who Geogebra-assisted TS-TS cooperative learning model is neither better nor the same as students who received TGT type cooperative learning.